The Influence of Competence and Synergy on the Performance of Kodam Jaya Personnel Mediated by Leadership - Sang Ketut Ratdimara; Rini Mulyani Sari (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Achmad Yani, 2025)
The purpose of this study is to establish harmonious cooperation between human resources within an agency or organization so that it can affect the performance of the agency, especially at the Jakarta Military Regional Command (Kodam Jaya). The method of analysis is done through explanatory research, with the application of PLS/SEM. Concepts and problems under study look at causality, then explain the variables causing the problem under study. The research sample was 123 Staff and Regional Military Command Officers of Kodam Jaya. The results of this study Competence has a positive effect on the performance of personnel at Kodam Jaya. Synergy has a positive effect on the performance of personnel at Kodam Jaya. Leadership has a positive effect on performance at Kodam Jaya. Competence and synergy have a positive effect on personnel performance at Kodam Jaya which is mediated by leadership, illustrating that competence, synergy and leadership at Kodam Jaya can have an influence on personnel performance at the Jakarta Military Regional Command.